72.12.7 problem 7

Internal problem ID [14854]
Book : DIFFERENTIAL EQUATIONS by Paul Blanchard, Robert L. Devaney, Glen R. Hall. 4th edition. Brooks/Cole. Boston, USA. 2012
Section : Chapter 3. Linear Systems. Exercises section 3.5 page 327
Problem number : 7
Date solved : Tuesday, January 28, 2025 at 07:17:42 AM
CAS classification : system_of_ODEs

\begin{align*} x^{\prime }\left (t \right )&=-2 x \left (t \right )-y\\ y^{\prime }&=x \left (t \right )-4 y \end{align*}

With initial conditions

\begin{align*} x \left (0\right ) = 1\\ y \left (0\right ) = 0 \end{align*}

Solution by Maple

Time used: 0.009 (sec). Leaf size: 21

dsolve([diff(x(t),t) = -2*x(t)-y(t), diff(y(t),t) = x(t)-4*y(t), x(0) = 1, y(0) = 0], singsol=all)
 
\begin{align*} x \left (t \right ) &= \left (t +1\right ) {\mathrm e}^{-3 t} \\ y &= t \,{\mathrm e}^{-3 t} \\ \end{align*}

Solution by Mathematica

Time used: 0.003 (sec). Leaf size: 24

DSolve[{D[x[t],t]==-2*x[t]-1*y[t],D[y[t],t]==1*x[t]-4*y[t]},{x[0]==1,y[0]==0},{x[t],y[t]},t,IncludeSingularSolutions -> True]
 
\begin{align*} x(t)\to e^{-3 t} (t+1) \\ y(t)\to e^{-3 t} t \\ \end{align*}